A method for preparing Ag@SNC nanocomposite material and modified electrode
Ag@SNC nanocomposites were prepared by one-step solid-phase ball milling method, which solved the problems of improved conductivity of perovskite materials and uneven distribution of modified materials, and achieved a high sensitivity and stability glucose electrochemical sensor, extending its service life.
Patent Information
- Application Number
- CN202211244519.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-12
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-10-12
AI Technical Summary
The existing technology has limited effect on the surface modification and modification methods for perovskite materials, resulting in limited improvement in conductivity and uneven distribution of modifications, hindering the diffusion of glucose macromolecules and affecting the performance of electrochemical sensors.
Ag@SNC nanocomposites were prepared by one-step solid-phase ball milling method, and silver metal nanoparticles were evenly distributed on the surface of perovskite material. The electrodes were modified by Ag@SNC nanocomposites to improve the conductivity of perovskite materials and enhance glucose. Current response.
It significantly improves the conductivity and electrocatalytic properties of perovskite materials, builds a high-sensitivity glucose electrochemical sensor, extends the service life and improves stability.
Smart Images

Figure CN115468998B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a preparation method of an Ag@SNC nanocomposite material and a modified electrode. Background Art
[0002] Diabetes is a common chronic disease with many complications and serious problems such as incurable diseases. Therefore, patients need to continuously monitor their blood sugar levels. Common methods for blood sugar testing include fingertip blood sampling, testing glycosylated hemoglobin, and continuous blood sugar testing. Among them, continuous blood sugar testing can record the patient's blood sugar level in all aspects of the day, such as high blood sugar after meals and low blood sugar at night, so as to provide certain guidance for the patient's treatment and self-blood sugar testing, greatly reducing the risk of diseases caused by diabetes. The most common material for continuous blood sugar monitors is electrochemical glucose sensors. Electrochemical glucose sensors have certain specificity for glucose and high sensitivity. They respond to changes in glucose concentration immediately with current, which is convenient for tracking patients' daily blood sugar levels and trends. They have certain advantages, so they are gradually becoming an important development material in continuous blood sugar monitors. Electrochemical glucose sensors are mainly divided into two categories: enzyme-based and non-enzyme-based sensors. The most commonly used first and second generation glucose sensors are mainly based on glucose enzymes. Glucose oxidase can catalyze glucose oxidation, cause current response, and detect the content of glucose in tissue fluid. However, glucose oxidase is easily interfered by factors such as ambient temperature and pH, resulting in irreversible enzyme inactivation, so its service life is limited and its stability is poor. Non-enzyme-based sensors, known as the fourth-generation technology, are based on materials such as precious metals such as Au, Ag, Pt, transition metal oxides, and conductive polymers. They have the advantages of high sensitivity, low cost, good selectivity, and good stability, and have broad application prospects.
[0003] Perovskite is a material with a stable octahedral crystal configuration. Its transition metal oxide perovskite material has the advantages of stable structure, diverse synthesis methods, and good corrosion resistance in alkaline environment. In recent years, it has attracted the attention of researchers as a glucose sensor material. Perovskite materials as glucose sensors have incomparable advantages over enzyme-based sensors, such as stable structure, good stability, and excellent redox reaction performance. However, the conductivity of perovskite materials as glucose sensors is poor and the reaction sites are limited. Therefore, researchers are committed to developing perovskite materials with multiple active sites and good conductivity. The cobalt element in cobalt-based perovskite oxides has variable valence states and high catalytic activity, and is also suitable for the decomposition of hydrogen peroxide. However, cobalt-based perovskite oxides have poor conductivity and often require modification and modification of the material surface. The current common method is to first prepare perovskite materials and then deposit precious metal nanoparticles on the surface of the material, or use carbon materials and perovskite materials to form composite materials. These methods have limited effect on improving the conductive properties of perovskite materials and are prone to cause excessive agglomeration of the modifiers, making it impossible for the modifiers to be evenly dispersed on the surface of the material, forming a large steric hindrance, and hindering the diffusion of glucose macromolecules to the surface of the material to participate in the reaction.
[0004] Therefore, how to use suitable modifiers to modify the surface of perovskite to improve the conductivity of perovskite materials, as well as suitable sample preparation methods to make the modifiers evenly distributed on the surface of perovskite materials has become a research hotspot. Summary of the invention
[0005] In order to overcome the technical problems that the existing methods for modifying and modifying the surface of perovskite materials have limited effects on improving the conductive properties of perovskite materials, and easily cause excessive agglomeration of the modifiers, so that the modifiers cannot be evenly dispersed on the surface of the material, forming a large steric hindrance, and hindering the diffusion of glucose macromolecules to the surface of the material to participate in the reaction, the present invention provides a method for preparing an Ag@SNC nanocomposite material and a modified electrode.
[0006] The technical solution of the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing an Ag@SNC nanocomposite material, comprising the following steps:
[0008] S1. Preparation of SNC precursor:
[0009] A one-step solid phase ball milling method is used to mix and ball mill a certain proportion of metal salts to form a SNC precursor solution, and the ball-milled SNC precursor solution is dried and ground to obtain a dry SNC precursor;
[0010] S2. Preparation of Ag@SNC nanocomposites:
[0011] The dried SNC precursor was placed in a muffle furnace and calcined at 800-1000° C. in an air atmosphere to obtain the Ag@SNC nanocomposite.
[0012] According to the above-mentioned method for preparing the Ag@SNC nanocomposite material, in step S1, the time for mixing and ball milling the metal salt is 10-14 hours.
[0013] According to the above-mentioned method for preparing the Ag@SNC nanocomposite material, in step S1, the ball-milled SNC precursor solution is dry-milled at a temperature of 60-80°C.
[0014] According to the above-mentioned method for preparing the Ag@SNC nanocomposite material, in step S1, the metal salt includes Ag salt, Sr salt and Nb salt, and the mass ratio of the Ag salt, Sr salt and Nb salt is 1:0.95:0.1.
[0015] According to the above-mentioned method for preparing the Ag@SNC nanocomposite material, in step S2, the calcination time is 8-12 hours.
[0016] According to the above-mentioned method for preparing the Ag@SNC nanocomposite material, in step S2, the calcination temperature is 950° C. and the calcination time is 10 h.
[0017] In a second aspect, the present invention provides a method for preparing an Ag@SNC nanocomposite modified electrode, comprising the following steps:
[0018] A1. Treatment of glassy carbon electrode:
[0019] The glassy carbon electrode is pre-polished before modification;
[0020] A2. Preparation of Ag@SNC nanocomposite modified electrodes:
[0021] A certain amount of the Ag@SNC nanocomposite prepared by the preparation method of the Ag@SNC nanocomposite is dispersed in ethanol, and a uniform suspension is obtained after ultrasonic dispersion. Then a certain amount of the suspension and nafion solution are sequentially dropped onto the surface of the glassy carbon electrode, and after drying, an Ag@SNC modified electrode is obtained.
[0022] According to the above-mentioned method for preparing the Ag@SNC nanocomposite modified electrode, in step A2, after the suspension and the nafion solution are dropped onto the surface of the glassy carbon electrode, it is dried in an oven at 30° C. for 2 h.
[0023] According to the above-mentioned method for preparing the Ag@SNC nanocomposite modified electrode, in step A2, the amount of the Ag@SNC nanocomposite is 1-10 mg, and the amount of ethanol is 1-10 mL.
[0024] According to the above-mentioned method for preparing the Ag@SNC nanocomposite modified electrode, in step A2, the ultrasonic dispersion time is 20-40 min.
[0025] According to the above-mentioned method for preparing the Ag@SNC nanocomposite modified electrode, in step A2, the amount of the suspension is 40 μL, and the amount of the nafion solution is 2 μL.
[0026] According to the above-mentioned method for preparing the Ag@SNC nanocomposite modified electrode, in step A2, the nafion solution is a nafion solution with a weight percentage of 0.05 wt%.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The invention adopts a one-step solid phase ball milling method to uniformly distribute silver metal nanoparticles on the surface of a perovskite material, and the surface of the perovskite material is modified and modified to obtain an Ag@SNC nanocomposite material, and the preparation material and method are simple; the silver metal nanoparticles have the advantages of small size, uniformity, high conductivity and biocompatibility, etc., and the surface modification of the perovskite material using conductive metal nanoparticles can effectively improve the conductivity of the perovskite material and enhance the current response to glucose, so that the Ag@SNC nanocomposite modified electrode prepared by the Ag@SNC nanocomposite has good electrocatalytic performance, and the constructed glucose electrochemical sensor has high sensitivity, high stability, long service life, and good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a comparison chart of the current response value test of four Ag@SNC nanocomposite modified electrodes of the present invention in 0, 4, 8, 12, and 16 mmol / L glucose solutions respectively. DETAILED DESCRIPTION
[0030] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0031] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device including a series of steps or units is not limited to the listed steps or units, but may optionally include steps or units not listed, or may optionally include other steps or units inherent to these processes, methods, products or devices.
[0032] Example 1: Preparation of Ag@SNC nanocomposites
[0033] The embodiment of the present invention provides a method for preparing an Ag@SNC nanocomposite material, comprising the following steps:
[0034] S1. Preparation of SNC precursor:
[0035] Ag salt, Sr salt and Nb salt with a mass ratio of 1:0.95:0.1 were mixed and ball-milled by a one-step solid-phase ball milling method, and a SNC precursor solution was formed after ball milling for 12 hours. The SNC precursor solution after ball milling was dried and ground at a temperature of 70°C to obtain a dry SNC precursor. In the above steps, ball milling for 12 hours can ensure that the metal salts are fully ball milled; the temperature of dry grinding is selected at 70°C, which can quickly dry the water and prevent the SNC precursor from reacting.
[0036] S2. Preparation of Ag@SNC (Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ ) Nanocomposites:
[0037] The dried SNC precursor was placed in a muffle furnace and calcined at 950°C for 10 hours in an air atmosphere to obtain the Ag@SNC nanocomposite. In the above steps, calcination in an air atmosphere is to image the perovskite; calcination for 10 hours can ensure that the material is fully imaged; the imaging temperature range of the Ag@SNC nanocomposite is 800-1000°C, and the imaging effect of the Ag@SNC nanocomposite is best when calcined at 950°C.
[0038] The preparation method of the Ag@SNC nanocomposite material adopts a one-step solid-phase ball milling method to evenly distribute silver metal nanoparticles on the surface of the perovskite material, and modify and modify the surface of the perovskite material to obtain the Ag@SNC nanocomposite material; the preparation materials and methods are simple, and the Ag silver nanoparticles are not only small and uniform in size, but also can be evenly distributed on the surface of the material, greatly improving the conductive properties of the perovskite material.
[0039] Example 2: Preparation of Ag@SNC nanocomposites
[0040] The present invention provides a method for preparing an Ag@SNC nanocomposite modified electrode, comprising the following steps:
[0041] A1. Treatment of glassy carbon electrode:
[0042] The glassy carbon electrode is pre-polished before modification. Since pre-polishing the glassy carbon electrode is a common technique in existing experiments, the present invention will not repeat the specific pre-polishing process.
[0043] A2. Preparation of Ag@SNC nanocomposite modified electrodes:
[0044] 2 mg of the Ag@SNC nanocomposite prepared in Example 1 was dispersed in 2 mL of ethanol and ultrasonically dispersed for 30 min to obtain a uniform suspension. Then 40 μL of the suspension and 2 μL of nafion (0.05 wt%) solution were dripped onto the surface of the glassy carbon electrode in sequence and dried in an oven at 30 °C for 2 h to obtain an Ag@SNC modified electrode.
[0045] Four Ag@SNC nanocomposite modified electrodes were prepared by the above-mentioned preparation method, and the current response values of the four Ag@SNC nanocomposite modified electrodes were tested in 0, 4, 8, 12, and 16 mmol / L glucose solutions, respectively. Figure 1 The following is a comparison chart of the current response values of four Ag@SNC nanocomposite modified electrodes tested in 0, 4, 8, 12, and 16 mmol / L glucose solutions. Figure 1 It can be seen that the four Ag@SNC nanocomposite modified electrodes all showed good linearity and high sensitivity. After that, the current response values of the four Ag@SNC nanocomposite modified electrodes were tested every three days, and it was found that three of the Ag@SNC nanocomposite modified electrodes could maintain stability for at least half a month.
[0046] The Ag@SNC nanocomposite modified electrode prepared using the Ag@SNC nanocomposite has few and simple operation steps, and the prepared Ag@SNC nanocomposite modified electrode has good electrocatalytic performance. The constructed glucose electrochemical sensor has high sensitivity, high stability, long service life, and has good application prospects.
[0047] Example 3: Preparation of Ag@SNC nanocomposite
[0048] The embodiment of the present invention provides a method for preparing an Ag@SNC nanocomposite material, comprising the following steps:
[0049] S1. Preparation of SNC precursor:
[0050] Ag salt, Sr salt and Nb salt with a mass ratio of 1:0.95:0.1 were mixed and milled by a one-step solid phase ball milling method, and a SNC precursor solution was formed after the mixed ball milling for 10 hours. The SNC precursor solution after ball milling was dried and ground at a temperature of 60°C to obtain a dry SNC precursor. In the above steps, ball milling for 10 hours can make the metal salts just complete the ball milling; the temperature of dry grinding is selected at 60°C, which can not only quickly dry the water, but also prevent the SNC precursor from reacting.
[0051] S2. Preparation of Ag@SNC (Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ ) Nanocomposites:
[0052] The dried SNC precursor was placed in a muffle furnace and calcined at 800°C for 14 hours in an air atmosphere to obtain the Ag@SNC nanocomposite. In the above steps, calcination in an air atmosphere is to image the perovskite; calcination for 14 hours can ensure that the material is fully imaged; the imaging temperature range of the Ag@SNC nanocomposite is 800-1000°C, and the Ag@SNC nanocomposite is just imageable when calcined at 800°C.
[0053] Example 4: Preparation of Ag@SNC nanocomposites
[0054] The present invention provides a method for preparing an Ag@SNC nanocomposite modified electrode, comprising the following steps:
[0055] A1. Treatment of glassy carbon electrode:
[0056] The glassy carbon electrode is pre-polished before modification. Since pre-polishing the glassy carbon electrode is a common technique in existing experiments, the present invention will not repeat the specific pre-polishing process.
[0057] A2. Preparation of Ag@SNC nanocomposite modified electrodes:
[0058] 1 mg of the Ag@SNC nanocomposite prepared in Example 3 was dispersed in 1 mL of ethanol and ultrasonically dispersed for 20 min to obtain a uniform suspension. Then, 40 μL of the suspension and 2 μL of nafion (0.05 wt%) solution were dripped onto the surface of the glassy carbon electrode in sequence and dried in an oven at 40°C for 1 h to obtain an Ag@SNC modified electrode.
[0059] Example 5: Preparation of Ag@SNC nanocomposite
[0060] The embodiment of the present invention provides a method for preparing an Ag@SNC nanocomposite material, comprising the following steps:
[0061] S1. Preparation of SNC precursor:
[0062] Ag salt, Sr salt and Nb salt with a mass ratio of 1:0.95:0.1 were mixed and milled by a one-step solid phase ball milling method, and the mixed ball milling was performed for 14 hours to form a SNC precursor solution. The SNC precursor solution after ball milling was dried and ground at a temperature of 80°C to obtain a dry SNC precursor. In the above steps, ball milling for 14 hours can ensure that the metal salts are fully ball milled; the temperature of dry grinding is selected at 80°C, which can not only quickly dry the water, but also prevent the SNC precursor from reacting.
[0063] S2. Preparation of Ag@SNC (Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ ) Nanocomposites:
[0064] The dried SNC precursor was placed in a muffle furnace and calcined at 1000°C for 10 hours in an air atmosphere to obtain the Ag@SNC nanocomposite. In the above steps, calcination in an air atmosphere is to image the perovskite; calcination for 10 hours can ensure that the material is just fully imaged; the imaging temperature range of the Ag@SNC nanocomposite is 800-1000°C, and calcination at 1000°C can accelerate the imaging time of the Ag@SNC nanocomposite.
[0065] Example 6: Preparation of Ag@SNC nanocomposites
[0066] The present invention provides a method for preparing an Ag@SNC nanocomposite modified electrode, comprising the following steps:
[0067] A1. Treatment of glassy carbon electrode:
[0068] The glassy carbon electrode is pre-polished before modification. Since pre-polishing the glassy carbon electrode is a common technique in existing experiments, the present invention will not repeat the specific pre-polishing process.
[0069] A2. Preparation of Ag@SNC nanocomposite modified electrodes:
[0070] 10 mg of the Ag@SNC nanocomposite prepared in Example 5 was dispersed in 10 mL of ethanol and ultrasonically dispersed for 40 min to obtain a uniform suspension. Then 40 μL of the suspension and 2 μL of nafion (0.05 wt%) solution were dripped onto the surface of the glassy carbon electrode in sequence and dried in an oven at 35 °C for 2 h to obtain an Ag@SNC modified electrode.
[0071] Example 7: Preparation of Ag@SNC nanocomposites
[0072] The embodiment of the present invention provides a method for preparing an Ag@SNC nanocomposite material, comprising the following steps:
[0073] S1. Preparation of SNC precursor:
[0074] Ag salt, Sr salt and Nb salt with a mass ratio of 1:0.95:0.1 were mixed and ball-milled by a one-step solid-phase ball milling method, and a SNC precursor solution was formed after ball milling for 12 hours. The SNC precursor solution after ball milling was dried and ground at a temperature of 70°C to obtain a dry SNC precursor. In the above steps, ball milling for 12 hours can ensure that the metal salts are fully ball milled; the temperature of dry grinding is selected at 70°C, which can quickly dry the water and prevent the SNC precursor from reacting.
[0075] S2. Preparation of Ag@SNC (Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ ) Nanocomposites:
[0076] The dried SNC precursor was placed in a muffle furnace and calcined at 900°C for 11 hours in an air atmosphere to obtain the Ag@SNC nanocomposite. In the above steps, calcination in an air atmosphere is to image the perovskite; calcination for 11 hours can ensure that the material is fully imaged; the imaging temperature range of the Ag@SNC nanocomposite is 800-1000°C, and the imaging effect of the Ag@SNC nanocomposite is better when calcined at 900°C.
[0077] Example 8: Preparation of Ag@SNC nanocomposites
[0078] The present invention provides a method for preparing an Ag@SNC nanocomposite modified electrode, comprising the following steps:
[0079] A1. Treatment of glassy carbon electrode:
[0080] The glassy carbon electrode is pre-polished before modification. Since pre-polishing the glassy carbon electrode is a common technique in existing experiments, the present invention will not repeat the specific pre-polishing process.
[0081] A2. Preparation of Ag@SNC nanocomposite modified electrodes:
[0082] 3 mg of the Ag@SNC nanocomposite prepared in Example 7 was dispersed in 6 mL of ethanol and ultrasonically dispersed for 40 min to obtain a uniform suspension. Then, 80 μL of the suspension and 4 μL of nafion (0.05 wt%) solution were dripped onto the surface of the glassy carbon electrode in sequence and dried in an oven at 30 °C for 3 h to obtain an Ag@SNC modified electrode.
[0083] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.
[0084] The above is an exemplary description of the present invention in conjunction with the accompanying drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A kind of Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ The application of nanocomposite modified electrode in glucose solution testing is characterized by: The following steps are involved: A1. Treatment of glassy carbon electrode: The glassy carbon electrode is pre-polished before modification; A2. Preparation of Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ Nanocomposite modified electrodes: A certain amount of Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ The nanocomposite material was dispersed in ethanol and ultrasonically dispersed to obtain a uniform suspension. Then a certain amount of the suspension and nafion solution were dripped onto the surface of the glassy carbon electrode in sequence. After drying, Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ Modified electrode, testing Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ Current response value of nanocomposite modified electrode in glucose solution; The Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ The method for preparing the nanocomposite material comprises the following steps: S1. Preparation of precursor: A one-step solid phase ball milling method is used to mix and ball mill a certain proportion of metal salts to form a precursor solution. The time for the metal salt mixing ball milling is 10-14 hours. The precursor solution after ball milling is dried and ground at a temperature of 60-80° C. to obtain a dry precursor. S2. Preparation of Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ Nanocomposites: The dried precursor was placed in a muffle furnace and calcined at 950 °C for 10 h in an air atmosphere to obtain Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ Nanocomposite materials.
2. The Ag@Sr according to claim 1 0.95 Nb 0.1 Co 0.9 O 3-δ The application of nanocomposite modified electrode in glucose solution testing is characterized by: In step A2, Ag@Sr 0.95 Nb 0.1 Co 0.9 O 3-δ The dosage of the nanocomposite material is 1-10 mg, and the dosage of the ethanol is 1-10 mL.
3. The Ag@Sr according to claim 1 0.95 Nb 0.1 Co 0.9 O 3-δ The application of nanocomposite modified electrode in glucose solution testing is characterized by: In step A2, the ultrasonic dispersion time is 20-40 min.
4. The Ag@Sr according to claim 1 0.95 Nb 0.1 Co 0.9 O 3-δ The application of nanocomposite modified electrode in glucose solution testing is characterized by: In step A2, the amount of the suspension used was 40 μL, and the amount of the nafion solution used was 2 μL.
5. The Ag@Sr according to claim 1 0.95 Nb 0.1 Co 0.9 O 3-δ The application of nanocomposite modified electrode in glucose solution testing is characterized by: In step A2, the nafion solution is a nafion solution with a weight percentage of 0.05 wt %.
